A generic encoding and operation scheme for mixed aperture three and four hexagonal discrete global grid systems. Issue 3 (4th March 2021) - Wang, R.; Ben, J.; Zhou, J.B.; Zheng, M. Y.
ABSTRACT: Discrete Global Grid Systems (DGGSs) are an emerging data model for integration and analysis of big Earth data. Current research on hexagonal DGGSs focuses mainly on the pure aperture, which limits application of resolution and may cause data redundancy. The mixed aperture hexagonal DGGS provides a new and flexible scheme that can optimize data precision by designing the most suitable grid resolution. This paper proposes a generic encoding and operation scheme for the mixed aperture 3 and 4 hexagonal DGGSs. A planar mathematical model with unique location representation was constructed. Based on this model, this paper designed an encoding scheme and gave relevant operational properties and rules. A generic method of extending the planar scheme to the surface of an icosahedron was then designed and spherical grids were obtained by projection. The conversion between geographical coordinates and codes was also provided. The proposed scheme has a more complete theoretical basis than existing schemes and can be applicable to different aperture sequences. Experiments show that the code addition efficiency of the proposed algorithm is superior to existing hexagonal grid systems. A case study with ocean salinity hexagonal data demonstrated the flexibility of the proposed scheme.